Information Overload in CSR Reports in China: An Exploratory Study - Danhong Wu; Sanja Pupovac (Australasian Accounting, Business and Finance Journal, 2019)
This paper is an exploratory analysis of information overload in a sample of 15 Chinese companies from mining, manufacturing, finance, electricity and information technology industries. Using an adaptation of Dahlsrud’s (2008) five dimensional framework of Corporate Social Responsibility (CSR) , we develop a longitudinal core information ratio analysis. Our findings suggest that while the length of the reports increased over the ten year period, the CSR information ratio, a measure of the proportion of the report comprising CSR disclosures, did not similarly increase. We argue that the driving force behind lengthy CSR reports is coercive pressure from the government and stock exchanges, and companies’ attempts to manage their stakeholders’ impressions. The results of this study have important implications for the Chinese government and Chinese stock exchanges as they consider ways to address and improve core CSR disclosures to be of greater value to users, rather than simply lengthier.
Keywords: information overload; CSR reports; China; coercive pressure; impression management